2009
DOI: 10.1242/dev.015974
|View full text |Cite
|
Sign up to set email alerts
|

Is left-right asymmetry a form of planar cell polarity?

Abstract: Consistent left-right (LR) patterning is a clinically important embryonic process. However, key questions remain about the origin of asymmetry and its amplification across cell fields. Planar cell polarity (PCP) solves a similar morphogenetic problem, and although core PCP proteins have yet to be implicated in embryonic LR asymmetry, studies of mutations affecting planar polarity, together with exciting new data in cell and developmental biology, provide a new perspective on LR patterning. Here we propose test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
71
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 109 publications
0
71
0
Order By: Relevance
“…G,H: Through an as-yet uncharacterized pathway, the localization of morphogens such as serotonin to the right side of the embryo suppresses downstream expression of genes (i.e., Nodal), which are thus expressed only on the left side (G), which eventually leads to asymmetric organ morphogenesis (H). This model can be readily extended to bodyplans where the midline is defined after the initial cleavages are complete by the spread of LR orientation information from coordinator cell(s) by means of planar cell polarity pathways (Aw and Levin, 2009;Vandenberg and Levin, 2010).…”
Section: Cilia and Nodal Flowmentioning
confidence: 99%
See 2 more Smart Citations
“…G,H: Through an as-yet uncharacterized pathway, the localization of morphogens such as serotonin to the right side of the embryo suppresses downstream expression of genes (i.e., Nodal), which are thus expressed only on the left side (G), which eventually leads to asymmetric organ morphogenesis (H). This model can be readily extended to bodyplans where the midline is defined after the initial cleavages are complete by the spread of LR orientation information from coordinator cell(s) by means of planar cell polarity pathways (Aw and Levin, 2009;Vandenberg and Levin, 2010).…”
Section: Cilia and Nodal Flowmentioning
confidence: 99%
“…This pathway has been most clearly elucidated in Xenopus, and involves a system of ion transporters, gap junctions, and serotonergic pathway elements that use electrophoresis to amplify intracellular chirality into multicellular gradients of a small molecule morphogen (Levin and Palmer, 2007;Aw and Levin, 2009). While the MTOC has not yet been molecularly dissected in this role, the other components (i.e., the asymmetric orientation and function of the cytoskeleton, transport proteins, ion transporters, and LR morphogens) are known in significant detail (Fig.…”
Section: Intracellular Mechanisms Origins and Evolution Of Early Cytomentioning
confidence: 99%
See 1 more Smart Citation
“…However, "ciliary" proteins, such as left-right dynein, known to be important for LR patterning, also have intracellular roles compatible with cilia-independent functions in laterality (9-12). In contrast to the nodal flow model, we have suggested that asymmetry is instead an ancient, well-conserved property of individual cells arising from the chirality of cytoskeletal structures that is subsequently amplified by physiological mechanisms (4,12,13). Thus, we sought the most evolutionarily distant model systems, and ones that are known not to rely on cilia for LR patterning, to test the hypothesis of fundamental molecular conservation of asymmetry mechanisms.…”
mentioning
confidence: 99%
“…In human beings, abnormalities in the proper development of laterality occur in more than 1 in 8,000 live births and often have significant medical consequences (1). Organ asymmetry is highly conserved among species; however, considerable controversy exists about the early steps of LR patterning among phyla (2)(3)(4) and the physical mechanisms that can break symmetry (5).…”
mentioning
confidence: 99%